Yellow Fever: The Challenges Ahead in India - Joshi, Mohan; Gumashta, Raghvendra; Kasturwar, N.B.; Junaid, Mohd. (National Journal of Community Medicine, 2012)
Looking into the vast threats of possible silent introduction of yellow fever virus into India, we have studied the various probable responsible factors, situations and circumstances along-with ways & means of ensuring adequate prevention cum control measures in case of any inadvertent identified presence of this virus in the Indian territories. Thus, recommended evidence based analytical approach, designed and implemented in word and spirit, will go a long way in generating confidence not only among the beneficiary general population of India, but will also give a sigh of relief from the possible grave public health threats of yellow fever to the policy makers, programme managers and health functionaries already overloaded with health care challenges of multiple types, dimensions and magnitude. A strategic policy initiative is the answer to address the critical issues based on suggestions deliberated herein.